Umbilical Cord Prolapse in the Prehospital Setting: A Case Report. (4th March 2022) - Chatelet, M.; Lemoine, L.; Balouet, P.; Eudier, F.; Saleh, A.; Delomas, T.; Amiot, F.
Abstract: Umbilical cord prolapse is an acute obstetric emergency associated with high fetal morbidity and mortality. To avoid poor outcomes, rapid diagnosis with immediate intervention is required, especially in the prehospital setting where resources are limited. In this case report, we describe a 38-year-old woman with umbilical cord prolapse, with a review of appropriate prehospital maneuvers and treatment.